2020
DOI: 10.26452/ijrps.v11ispl4.4295
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the prevalence of osteoporosis among children with hemophilia and its relation to serum 25(oh) vitamin D and serum rankl

Abstract: Osteoporosis is one of the comorbidities that complicating hemophilia. Recurrent hemarthrosis, chronic arthropathy and immobilization all are factors that make patients with hemophilia prone to this complication. Till recently the major emphasis of the osteoporosis diagnosis is the dual-energy X-ray absorptiometry (DEXA) scan, however, the definition of osteoporosis in pediatrics not only low bone mineral density measured by DEXA scan but also required the presence of clinically significant fracture history. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…16 studies [ 17 22 , 24 28 , 30 , 31 , 33 35 ] examined BMD of lumbar spine (LS), 6 [ 20 , 22 , 24 , 26 , 27 , 31 ] examined BMD of femoral neck (FN), and 6 [ 19 , 26 , 27 , 31 , 33 , 35 ] examined BMD of total hip (TH). 12 [ 17 22 , 24 28 , 34 ], 5 [ 20 , 22 , 24 , 26 , 27 ], and 3 [ 19 , 26 , 27 ] studies reported the data of LS, FN, and TH BMD presented as standard deviation, respectively. Of the included studies, 9 [ 19 , 20 , 22 , 24 , 25 , 30 , 31 , 33 , 35 ] recruited patients from Asia, 3 [ 23 , 26 , 27 ] from Europe, 4 [ 18 , 28 , 32 , 34 ] from Africa, 1 [ 17 ] from Australia, 1 [ 21 ] from North America, and 1 [ 29 ] from South America.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…16 studies [ 17 22 , 24 28 , 30 , 31 , 33 35 ] examined BMD of lumbar spine (LS), 6 [ 20 , 22 , 24 , 26 , 27 , 31 ] examined BMD of femoral neck (FN), and 6 [ 19 , 26 , 27 , 31 , 33 , 35 ] examined BMD of total hip (TH). 12 [ 17 22 , 24 28 , 34 ], 5 [ 20 , 22 , 24 , 26 , 27 ], and 3 [ 19 , 26 , 27 ] studies reported the data of LS, FN, and TH BMD presented as standard deviation, respectively. Of the included studies, 9 [ 19 , 20 , 22 , 24 , 25 , 30 , 31 , 33 , 35 ] recruited patients from Asia, 3 [ 23 , 26 , 27 ] from Europe, 4 [ 18 , 28 , 32 , 34 ] from Africa, 1 [ 17 ] from Australia, 1 [ 21 ] from North America, and 1 [ 29 ] from South America.…”
Section: Resultsmentioning
confidence: 99%
“…12 [ 17 22 , 24 28 , 34 ], 5 [ 20 , 22 , 24 , 26 , 27 ], and 3 [ 19 , 26 , 27 ] studies reported the data of LS, FN, and TH BMD presented as standard deviation, respectively. Of the included studies, 9 [ 19 , 20 , 22 , 24 , 25 , 30 , 31 , 33 , 35 ] recruited patients from Asia, 3 [ 23 , 26 , 27 ] from Europe, 4 [ 18 , 28 , 32 , 34 ] from Africa, 1 [ 17 ] from Australia, 1 [ 21 ] from North America, and 1 [ 29 ] from South America. Among the included studies, in 10 studies [ 17 , 18 , 21 , 23 , 25 , 28 , 30 , 32 , 34 , 35 ], mean age was less than 18 years and in 8 [ 19 , 20 , 22 , 24 , 26 , 27 , 31 , 33 ] studies more than 18 years, and one study [ 29 ] did not report mean age.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation